EFFECTS OF ELK HERBIVORY ON VEGETATION AND NITROGEN PROCESSES - SCHOENECKER, KATHRYN A; SINGER, FRANCIS J; ZEIGENFUSS, LINDA C; BINKLEY, DAN; MENEZES, ROMULO S. C (The Journal of wildlife management, 2004)
We used 35-year and 4-year ungulate exclosures to determine the effects of elk (Cervus elaphus) herbivory on above-ground and below-ground production and soil fertility on the elk winter range in Rocky Mountain National Park (RMNP), Colorado, USA. We used paired grazed and ungrazed plots to evaluate ungulate herbivory effects in short and tall willow (Salix spp.), aspen (Populus spp.), and upland grass/shrub vegetation associations. We measured nitrogen (N) fluxes (litter deposition, fecal and urinary deposition from elk, movements of N by elk, N mineralization, soil N availability, elk consumption rates) within the elk winter, above-ground and below-ground N pools (herbaceous, shrub and root biomass, %N in plants, roots, and soil), and N fluxes on and off the elk winter range (seasonal movement of N by elk). Nitrogen mineralization and soil nitrate (NO3) pools were reduced in the short willow community (P = 0.07 and 0.10, respectively; n = 4 sites) in grazed plots, but not in the upland grass/shrub community or tall willow sites (P >0.10). Annual growth of willows was reduced by 98% in grazed plots, relative to 35-year exclosures, and 66% relative to 4-year exclosures. Thus, height, canopy size, and litter biomass of willows were reduced, and N yield of willows was 64% less in grazed plots. We evaluated movement of N by elk among 6 major vegetation associations and found that elk grazed more and bedded less in willow vegetation association compared to mixed conifer, mesic meadow, and grassland/shrub associations (P = 0.014, 0.001, and 0.026, respectively), suggesting that elk herbivory and movement led to a net loss of N in the willow vegetation association. Elk spent less total time in willows than mesic meadow association, yet they consumed large amounts of willow plant biomass. We recommend management of elk numbers and elk herbivory that takes into consideration impacts to N process function, as negative effects from current levels of herbivory were observed in ≥1 of 3 vegetation associations studied.